Modulation of transepithelial electric resistance (TEER) in reconstructed human epidermis by excipients known to permeate intestinal tight junctions. Issue 9 (14th July 2015) - Abdayem, Rawad; Callejon, Sylvie; Portes, Pascal; Kirilov, Plamen; Demarne, Frédéric; Pirot, Fabrice; Jannin, Vincent; Haftek, Marek
Abstract Several excipients are commonly used to enhance the drug absorption through simple epithelia of the digestive tract. They permeate the paracellular barrier constituted by tight junctions (TJs). We compared the effects of two excipients, sodium caprate (C10) and a self‐emulsifying excipient Labrasol composed of a mixture of caprylocaproyl polyoxyl‐8 glycerides, both applied to emerged reconstructed human epidermis either 'systemically', that is by addition to the culture medium, or topically. During the 'systemic' application, which produced cytoplasmic translocation of occludin and leakage of the biotin marker into the lower stratum corneum, the decrease in the trans‐epithelial electrical resistance (TEER) was less abrupt with Labrasol when compared with C10, even though both excipients produced comparable final effects over time. With topical Labrasol, a significant TEER decrease was obtained with 5 times the 'systemic' concentrations. Topical application of C10 also resulted in the loss of the barrier function measured with TEER but had dramatic deleterious effects on the tissue morphology observed with light and electron microscopy. Our study demonstrates the potential value of Labrasol as an enhancer of bioavailability of molecules applied through the transcutaneous route. Our results suggest modulation of the epidermal TJs by both compounds. Even though the C10 action was at least partly due to overall cell damage and despite the fact that the decrease in TEER after topical application was apparently related to the permeabilization of the primary barrier of the stratum corneum in the first place.